2021
DOI: 10.31234/osf.io/pwhb9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Information Dissemination and the COVID-19 Pandemic: The Relationship between Different Information Sources and Symptoms of Psychopathology

Abstract: The 2020-2021 COVID-19 pandemic has added to the mental health strain on individuals and groups across the world. Viral mitigation protocols and viral spread affect millions every day, but to widely different degrees. How individuals gather information about the pandemic might have an effect on levels of mental distress in the population. In this cross-sectional and representative study of the adult population of Norway, findings suggest that information gathered through newspapers and social media are the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…News coverage and publicly available information about COVID-19 play an important role in perceptions of risk and subsequent preventive behaviors. Previous research has indicated that only specific types of media engagement (ie, news from official government or health organizations) are related to preventive behaviors but that COVID-19 news consumption increases anxiety and distress regardless of platform or media source [ 11 , 26 , 27 ]. These findings illuminate the importance of accurate and easily accessible news about the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…News coverage and publicly available information about COVID-19 play an important role in perceptions of risk and subsequent preventive behaviors. Previous research has indicated that only specific types of media engagement (ie, news from official government or health organizations) are related to preventive behaviors but that COVID-19 news consumption increases anxiety and distress regardless of platform or media source [ 11 , 26 , 27 ]. These findings illuminate the importance of accurate and easily accessible news about the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…A nationally representative, cross-sectional survey found that consuming news about COVID-19 was associated with greater psychological distress in the week following the implementation of stay-at-home orders in the United States [ 8 ]. Individuals who reported following the news “very closely” reported the highest levels of distress, which were associated with increases in perceived threat of the virus [ 8 , 11 , 26 ]. Greater frequency and duration of engagement with news about COVID-19 are associated with symptoms of anxiety and depression regardless of source, with individuals who consume COVID-19-related media across multiple platforms reporting the greatest increases in symptom severity [ 7 , 27 ].…”
Section: Introductionmentioning
confidence: 99%